2022
DOI: 10.1016/j.jbc.2022.101667
|View full text |Cite
|
Sign up to set email alerts
|

Xenophagy of invasive bacteria is differentially activated and modulated via a TLR-TRAF6-Beclin1 axis in echinoderms

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 75 publications
1
7
0
Order By: Relevance
“…These results collectively indicated that m6A methylation modification served as a positive regulator in V. splendidus -induced coelomocytes autophagy. Autophagy in A. japonicus can resist V. splendidus infection, as has been proven in our previous research 24 , 25 . To further demonstrate the immunological function of m6A in response to V. splendidus infection, we detected bacterial abundance in coelomocytes.…”
Section: Resultssupporting
confidence: 67%
See 3 more Smart Citations
“…These results collectively indicated that m6A methylation modification served as a positive regulator in V. splendidus -induced coelomocytes autophagy. Autophagy in A. japonicus can resist V. splendidus infection, as has been proven in our previous research 24 , 25 . To further demonstrate the immunological function of m6A in response to V. splendidus infection, we detected bacterial abundance in coelomocytes.…”
Section: Resultssupporting
confidence: 67%
“…Some researchers found autophagy can help hosts to defend against pathogenic infection 26 . Our previous studies showed that the autophagy activity and m6A methylation level of coelomocytes significantly increased during V. splendidus infection of A. japonicus 24 , 25 , 27 , 28 . However, the relationship between autophagy and m6A methylation was not addressed.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…It protects host cells from lethal damage, and plays a key role in innate immunity (Cong et al, 2020). Xenophagy, promotes macrophage clearance of cytoplasmic invaders after pathogenic DNA exposure or phagocytic membrane disruption by pathogens (Shao et al, 2022). A total of 8 papers are collected in this topic, expounding the role of xenophagy in animal viral and bacterial infections.…”
mentioning
confidence: 99%